2011
DOI: 10.1007/s12149-011-0482-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adding high-dose In-111 octreotide therapy during Sandostatin treatment in patients with disseminated neuroendocrine tumors: clinical results of 14 patients

Abstract: High-dose In-111 octreotide can be safely administered in conjunction with somatostatin analogue in patients with disseminated NET and this treatment may help to stabilize the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…111 In, emitting 1.84 gamma ray photons per decay, with a convenient for SPECT energy 171 and 245 keV is the radioisotope which can be considered as a theranostic agent upon attachment to the appropriate targeting biomolecule ( Levine and Krenning, 2017 ; Pencharz et al, 2018 ). In this way beginning with Krenning’s work ( Krenning et al, 1994 ) it had been being demonstrated that using therapeutic doses of the radiopharmaceutical [ 111 In-DTPA]- D -Phe 1 -octreotide ( 111 In-octreotide) for treatment of neuroendocrine tumors does not lead to severe side effects ( Janson et al, 1999 ; Caplin et al, 2000 ; Anthony et al, 2002 ; Valkema et al, 2002 ; Buscombe et al, 2003 ; Nguyen et al, 2004 ; Kong et al, 2009 ; Ozkan et al, 2011 ). More than 140 cases of therapy using this radiopharmaceutical are analyzed in these papers.…”
Section: Introductionmentioning
confidence: 99%
“…111 In, emitting 1.84 gamma ray photons per decay, with a convenient for SPECT energy 171 and 245 keV is the radioisotope which can be considered as a theranostic agent upon attachment to the appropriate targeting biomolecule ( Levine and Krenning, 2017 ; Pencharz et al, 2018 ). In this way beginning with Krenning’s work ( Krenning et al, 1994 ) it had been being demonstrated that using therapeutic doses of the radiopharmaceutical [ 111 In-DTPA]- D -Phe 1 -octreotide ( 111 In-octreotide) for treatment of neuroendocrine tumors does not lead to severe side effects ( Janson et al, 1999 ; Caplin et al, 2000 ; Anthony et al, 2002 ; Valkema et al, 2002 ; Buscombe et al, 2003 ; Nguyen et al, 2004 ; Kong et al, 2009 ; Ozkan et al, 2011 ). More than 140 cases of therapy using this radiopharmaceutical are analyzed in these papers.…”
Section: Introductionmentioning
confidence: 99%
“…Partial response was reported in 4% to 7.1%, stable disease in 17.9%-28% and progressive disease in 50%-56%[ 56 ]. Another study of 14 patients with metastatic NETs who received indium in-111 octreotide showed stable disease in 50 % of cases, partial response in 14%, and disease progression in 36%[ 64 ]. A quality-of-life study in 13 of these patients found a significant benefit in this[ 65 , 66 ].…”
Section: Treatment/managementmentioning
confidence: 99%